NILAI KEMANFAATAN UTILITARIAN TERHADAP BATASAN USIA NIKAH (Studi Komparasi UU No. 16 Tahun 2019 & KUH Perdata) - Darajat Ahlan Solihin; Masrokhin Universitas Hasyim Asy'ari (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Value of Utilitarian Benefits, Againts Mariage Age Limits (Comparative Study Of Law No. 19 of 2019 & The Civil Code).” This research aim to answer question that arise in the general public, what is the value of the benefit that exist in the theory of Utilitarian benefits, how is the review of law No.16 of 2019 & The Civil code regarding the age limit for marriage, wich provides greeter benefits between law no 16 of 2019 with the civil code. The type of research used in this research is Library research with a qualitative approach. The metod of data collection is by using documentation, interviews, and observation techniques. The result of this study produce the value of the benefits, a review of law no.16 of 2019, and the civil code on the Marriage age limits, as well as the domination of the benefits between law no. 16 of 2019 & The Civil code when Justapoxed with The Utilitarian Theory.